The root cause of Indonesia environment degradation : an Islamic economics perspective. - Setya Hardi, Amirullah; Widodo, Tri; Putriani, Diyah; Kayadibi, Saim (2012)
This research paper attempts to observe the root cause of deforestation in Indonesia from Islamic economics point of view. By employing historical approach and policy study analysis, this research shows that only 3.29 percent of critical land which has been rehabilitated. Many researches proved that there is positive relationship between external debt and deforestation. Islam discourage Muslim Ummah start their “life” by borrowing money, including in the state level. It is awarded that wealth as one of the maqasid al-shari’ah elements will never be able to be protected since a country is charged by the debt along with the interest portion. Therefore, the root cause of natural calamity in environment is originally “created” by human being’ decision. Since the government, as the ulul ‘amr, agree to deal with economy interest rate based system, hence the disaster will be “created”.